A framework for the design of digital games with therapeutic potential by people in recovery from Substance Use Disorders - Souza, Paula Maia de (2023)
Concerns related to mental health have been spread worldwide and computing has demanded efforts in the development of solutions to support therapies for mental disorders. Substance Use Disorders (SUDs) are no longer being treated as an individual health issue, but are also related to public and social health. Patients in recovery from SUDs are end users of therapy support systems and their involvement in the process of creating these computer systems has the potential to increase patients' autonomy and help with adherence to therapy. Studies involving the participation of end users in the construction of therapeutic systems were identified in the literature, however, in these studies, health professionals and patients participate more as information providers. Little is known about this population actively participating in the design of therapeutic solutions, more specifically, digital games with therapeutic potential. Considering this context, the motivation for this doctoral research arose from the intention to formalize a framework that could scale the design and development of digital games with therapeutic potential by people recovering from SUDs. The hypothesis was that delivering a specific design process for this population would increase the autonomy and empowerment of end users (health professionals and patients). Given the motivation to support the design and development of digital games with therapeutic potential for people recovering from SUDs, the objective of this doctoral research was to build a framework that corroborates the design and development activities by this population, providing more autonomy to those end users. In order to achieve this objective, the methodological path included, first, a Systematic Mapping (SM) carried out on computing in support of the therapy of mental disorders. In parallel, a case study was carried out with people recovering from SUDs at a Psychosocial Care Center - Alcohol and Drugs (CAPS-AD). Based on the results of the SM and the case study, it became possible to identify demands for the construction of the framework. To build the framework, the following were defined: i) a design process; ii) a set of rules for creating Conversational Agents (CAs) that can guide the end user in the design process; and iii) a web platform with an embedded CA to support the design process. After completing the development of the framework, a second case study was carried out, at CAPS-AD in another city, to evaluate the framework. The results suggest that the use of the proposed framework aroused more interest, engagement, autonomy, and empowerment of end users in the design of digital games with therapeutic potential. The main contributions of this doctoral thesis are i) State-of-the-art study on computing to support the therapy of mental disorders; ii) Lessons learned from applying a design process by people in recovery from SUDs in a real-life setting; iii) Construction of a framework for the design of digital games with therapeutic potential by people in recovery from SUDs; and iv) Evaluation of the framework with end users in recovery from SUDs.